Environmental DNA reveals arboreal cityscapes at the Ancient Maya Center of Tikal - David L. Lentz (Nature Portfolio, 2021)
Abstract Tikal, a major city of the ancient Maya world, has been the focus of archaeological research for over a century, yet the interactions between the Maya and the surrounding Neotropical forests remain largely enigmatic. This study aimed to help fill that void by using a powerful new technology, environmental DNA analysis, that enabled us to characterize the site core vegetation growing in association with the artificial reservoirs that provided the city water supply. Because the area has no permanent water sources, such as lakes or rivers, these reservoirs were key to the survival of the city, especially during the population expansion of the Classic period (250–850 CE). In the absence of specific evidence, the nature of the vegetation surrounding the reservoirs has been the subject of scientific hypotheses and artistic renderings for decades. To address these hypotheses we captured homologous sequences of vascular plant DNA extracted from reservoir sediments by using a targeted enrichment approach involving 120-bp genetic probes. Our samples encompassed the time before, during and after the occupation of Tikal (1000 BCE–900 CE). Results indicate that the banks of the ancient reservoirs were primarily fringed with native tropical forest vegetation rather than domesticated species during the Maya occupation.